The Role of Social Entrepreneurship Through Economic Empowerment of Island Communities - Pahrul, Pahrul; Mahmuddin, Mahmuddin; Tahir, Sumiati; Wisudawaty, Ika; Yunus, Irfan (International Journal of Education, Vocational and Social Science, 2024)
This research aims to reveal the role of entrepreneurship in community empowerment on Kulambing Island, Pangkep Regency. Social entrepreneurship is understood as an approach based on collaboration, innovation and creation in creating economic activities that support improving community welfare. This research uses a qualitative approach with descriptive methods, involving 9 informants selected through purposive sampling techniques. The research results show that the role of social entrepreneurship, such as making Moringa leaf chips, doi-doi cakes, managing dried fish, and women's schools, has succeeded in empowering communities and creating new economic opportunities. Collaboration between society, government, business and non-governmental organizations is an important factor in overcoming resource challenges and social change. These findings confirm that social entrepreneurship has a significant role in reducing social problems, improving the quality of life, and contributing to sustainable development.